Answer:
$33,090.
Step-by-step explanation:
The formula is A = P( 1 + r/2)^2n so we have:
50,000 = P(1 + 0.07/2)^(6*2)
50000 = P * 1.035^12
P = 50000/ 1.035^12
= $33,090 to the nearest dollar.
Problem One
Find AM
AM = 71.5 - 22 = 49.5
Step Two
State the Givens.
AM = 49.5
MN = 71.5
MB = x
MP = 97.5
Step Three
Set up the Proportion
AM : NM :: x : PM
49.5 : 71.5 :: x : 97.5
Substitute and solve
49.5 / 71.5 = x / 97.5 Cross Multiply
49.5 * 97.5 = 71.5 * x Combine the numbers on the left.
4860.375 = 71.5 * x Divide by 71.5
4860.375 / 71.5 = x
x = 67.98
Problem Two
Remark
This is just a straight application of the Pythagorean Theorem
a^2 + b^2 = c^2
a = 10
b = 24
c = ??
10^2 + 24^2 = c^2
100 + 576 = c^2
676 = c^2
sqrt(c^2) = sqrt(676)
c = 26 <<<< answer
Answer:
5
Step-by-step explanation:
[math]
U_{n} = 5n - 2 \\
Common Difference = U_{n+1} - U_{n} \\
= [5(n + 1) - 2] - [5n - 2] = [5n + 5 - 2] - [5n - 2]\\
= 5n + 5 - 2 - 5n + 2\\
= 5
[/math]
Answer:
y = 56
Step-by-step explanation:
the midsegment SV is half the length of the side TU , that is
y - 9 =
(y + 38) ← multiply both sides by 2 to clear the fraction
2y - 18 = y + 38 ( subtract y from both sides )
y - 18 = 38 ( add 18 to both sides )
y = 56
------------------------------------------------------------------------------------------
Equation
------------------------------------------------------------------------------------------
y = -3x - 9
------------------------------------------------------------------------------------------
Option 1
------------------------------------------------------------------------------------------
If I substitute x = -9, I should get y = 0
When x = -9
y = -3 (-9) - 9
= 18 (I did not get 0, wrong)
------------------------------------------------------------------------------------------
Option 2
------------------------------------------------------------------------------------------
If I substitute x = -3, I should get y = 0
y = -3(-3) - 9
y = 9 - 9
y = 0 (Yes, I got 0, correct)
------------------------------------------------------------------------------------------
Option 3
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -3
y = -3 (0) - 9
y = 0 - 9
y = -9 (I did not get -3, wrong)
------------------------------------------------------------------------------------------
Option 4
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -9
y = -3 (0) - 9
y = 0 - 9
y = -9 (Yes, I got -9, correct)
------------------------------------------------------------------------------------------
Answer: (-3, 0) and (0, 9) are ordered pairs of the equation (Answer B, D)
------------------------------------------------------------------------------------------